PERANCANGAN ALAT BANTU UNTUK MEMINIMALISIR PANAS PADA RUANG PRODUKSI CV. IKHWANUDIN BERDASARKAN ANALISIS LINGKUNGAN KERJA DAN BEBAN KERJA MENGGUNAKAN VALUE ENGINEERING - Suryani; Iksan Adiasa; Nurul Hudaningsih; Koko Hermanto (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
CV. Ikhwanudin is a company engaged in tofu production in Sumbawa Regency which was founded in 2013. CV. Ikhwanudin has a fairly large production site with a production capacity of 150 kg of soybeans per day. Based on the results of observations, it is known that the working environment temperature was 45.8°C in the CV production room. Ikhwanudin. The environmental temperature is higher than the worker's body temperature. Based on work environment problems at CV. Ikhwanudin, it is necessary to design equipment to minimize heat in the tofu production room. Workload is measured using a Visual Analogue Scale (VAS) questionnaire and designing tools to minimize worker burden due to the work environment using the Value Engineering (VE) method. Based on the calculation results of the working environment temperature at CV. Ikhwanudin is quite high, namely an average of 34.80 degrees because there are 5 tofu cooking stoves in the production room. , Workload of workers at CV. Ikhwanudin is quite high so improvements need to be made. There is no significant influence between the work environment and workload based on the results of the correlation test and tools with values of 4.9 x 10-4, 7.4 x 10-2, 2, are obtained. 3x10-3 based on proposal 1 with a very low cost of IDR 7,650,000.